No home movies - Karrer, Michael (Iberoamericana Vervuert, 2025)
Argentine and Brazilian documentary cinema is experiencing a recent trend that is characterized by a growing use of audiovisual material of private and family origin. Until now, this creative practice based on family archives has received little attention in Latin American documentary studies, despite being very productive both in the region and beyond. Based on a detailed study of four documentaries considered paradigmatic for their respective contexts —Papirosen (2011), by Gastón Solnicki; In the Intense Now (2017), by João Moreira Salles; Elena (2012), by Petra Costa and Silence Is a Falling Body (2017), by Agustina Comedi—analyzes how the use of films or home videos, at first glance very personal, it is not only usually accompanied by a politicized reading of the family past. Furthermore, the use of the family archive as a "counter-archive" in these films can be understood as an important element in the construction of political and social meanings in contemporary documentary. The films examined offer new approaches to a wide range of topics ranging from the aftermath of the Shoah to overcoming personal trauma, from the major political events of the 20th century to the micropolitics of the body and gender. At the same time, they question the traditional notion of "political cinema" and expand the spectrum of what can be considered political in documentary film.